The Norton anthology of American literature (Norton, 1986)
The aim of this shorter edition is to provide teachers and students of American literature with all the material they require in a single volume. The anthology makes available to readers the rich diversity of American literature and has been revised to include more work by such authors as Benjamin Franklin, Ralph Waldo Emerson, Nathaniel Hawthorne and Henry Thoreau. 15 new poets are represented, including Robert Duncan, Denise Levertov and Robert Creeley, and poets from the American West such as Richard Hugo. There is also additional material by women writers and six Afro-American authors